2014
DOI: 10.1039/c4cs00097h
|View full text |Cite|
|
Sign up to set email alerts
|

Polyoxometalate based open-frameworks (POM-OFs)

Abstract: Polyoxometalate-based open frameworks (POM-OFs) are extended architectures incorporating metal-oxide cluster units and comprise an emergent family of materials with a large diversity of topologies, structural flexibility and functionality at the nanoscale. Not only do POM-OFs present a wide range of configurable structures, but also a have a vast array of physical properties which reflect the properties of the various 'modular' molecular inputs. Here we describe the methodologies that can be used to construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
248
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(257 citation statements)
references
References 117 publications
0
248
0
9
Order By: Relevance
“…There are seven types (OA-OG in Figure 3) of possible protonation sites, taking account of the D2h symmetry. The solution-state 17 O NMR spectra of [V10O28] 6− (enriched by the addition of H2 17 O) show an up-field shift of the 17 O NMR signals assignable to OB and OC upon acidification with HCl [71,74]. It has been reported that the protonation of oxygen atoms in POMs [38,55,56].…”
Section: Isopolyoxometalatesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are seven types (OA-OG in Figure 3) of possible protonation sites, taking account of the D2h symmetry. The solution-state 17 O NMR spectra of [V10O28] 6− (enriched by the addition of H2 17 O) show an up-field shift of the 17 O NMR signals assignable to OB and OC upon acidification with HCl [71,74]. It has been reported that the protonation of oxygen atoms in POMs [38,55,56].…”
Section: Isopolyoxometalatesmentioning
confidence: 99%
“…Protons of crystalline H3PW12O40·6H2O are present as the hydrated species, H5O2 + , each of which links four neighboring POMs by hydrogen bonding to the terminal W-O oxygen atoms [21]. For anhydrous H3PW12O40, the protons have been reported to be attached to the most basic bridging oxygen atoms based on infrared (IR) and 17 O NMR spectroscopy results [21]. Himeno and co-workers reported that the potential difference between the first one-and two-electron redox waves of cyclic voltammograms served as a useful criterion for the basicity of Keggin anions [85,86] …”
Section: Heteropolyoxometalatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their formation is mainly based on the appropriate charge to ionic radius ratio and charge density which: (i) prohibits infinite polymerization; (ii) promotes formation of π-bonds with the O 2− ligands; (iii) exhibits flexible and various coordination geometries. In the past decades, the properties of POMs have been extensively investigated due to a wide range of composition, sizes, rich redox chemistry, charge distribution and photochemistry to fulfill specific requirements in a variety of applications, including functional materials in catalysis, molecular electronics, magnetism, materials science and medicine [28][29][30][31]. Based on the above observations, various groups reported their efforts to design POM-based heterogeneous catalytic systems for the promotion of specific reactions.…”
Section: Pom-ldh Composite Materialsmentioning
confidence: 99%
“…The interplay of supramolecular interactions (through hydrogen bonds, van der Waals forces), as well as reactivity between POM clusters and transition metals or metal complexes, can lead to the formation of extended networks of coordinatively linked 1D chains, 2D sheets and 3D compounds. As shown in the figure below, the POM clusters can be linked through transitional metals (TM) via grafted organic units, directly through transition metals, through organic linkers and through organic linkers via transition metals ( Figure 8) [50]. POM-OFs are porous materials with interesting structural flexibility, stability and interesting physical properties.…”
Section: Pom-ofsmentioning
confidence: 99%